Cigarette Smoking Increases the Risk for Subgingival Infection With Periodontal Pathogens - Zambon, J J; Grossi, S G; Machtei, E E; Ho, A W; Dunford, R; Genco, R J (Journal of periodontology (1970), 1996)
Cigarette smoking has been found to increase the risk for periodontitis. The present study examined the association between cigarette smoking and subgingival infection with periodontal pathogens to determine if smokers are more likely to be infected with certain periodontal pathogens than non-smokers. Self-reported data on 1,426 subjects, aged 25 to 74, from the Erie County Study were obtained including data on 798 subjects who were current or former smokers. Mean clinical attachment loss was used to estimate the severity of periodontal destruction. Subgingival infection with target periodontal pathogens was determined by indirect immunofluorescence microscopy. Smokers harbored significantly higher levels and were at significantly greater risk of infection with Bacteroides forsythus than non-smokers. Adjusting for disease severity, the risk of subgingival infection with B. forsythus in current smokers was 2.3 times that of former smokers or non-smokers. The relative risk of B. forsythus infection also increased 1.18 times for every category of smoking as the amount of smoking measured in packyears increased from very light to heavy. Adjusting for disease severity, Porphyromonas gingivalis was also more likely to subgingivally infect smokers than non-smokers; however, there was not a significantly higher relative risk for infection with this bacterium. The data from this study indicate that cigarette smoking increases the likelihood of subgingival infection with certain periodontal pathogens. This may partly explain the increased risk for periodontitis seen in smokers. J Periodontol 1996;67:1050-1054.